Fostering an enabling environment for Learners with Special Needs in rural primary schools in Lesotho - Mathabo Lebona; Mohapi Augustinus Monyane; Kananga Robert Mukuna (International Journal of Studies in Inclusive Education)
Successful inclusion of Learners with Special Educational Needs in mainstream teaching and learning is a challenge globally. This study explores fostering an enabling environment for Learners with Special Educational Needs in rural primary schools in Lesotho. Data for the study were collected using a qualitative approach using a case study design, and analysis was done through Thematic Analysis. Thirteen teachers from two primary schools in the rural community and two officials from the Ministry of Education and Training purposively were selected in Lesotho and participated in this study. Focus group discussions and one-on-one semi-structured interviews were used as instruments for data collection. Thematic results showed that teachers’ inflexibility hindered the creation of an enabling environment in terms of infrastructure and poor allocation of resources, which were critical challenges to support LSEN in their daily teaching and learning activities. The results revealed that not enabling environments and the unavailability of relevant resources increase the number of dropouts in schools among LSEN. The results further revealed that the lack of pertinent training for regular teachers to help special education learners succeed effectively handicapped the education of LSEN in mainstream teaching and learning. Therefore, the study recommends that teachers be given continuous workshops by MoET and in-service training to fill the gaps in special education programmes and produce teachers who can be relevant in inclusive teaching and learning in Lesotho's primary mainstream schools, particularly rural schools.